Gender and equitable benefit-sharing mechanisms through Agricultural Innovation Platforms in Rwanda. Issue 4 (8th August 2018) - Adam, Rahma I.; Misiko, Michael; Dusengemungu, Leonidas; Rushemuka, Pascal; Mukakalisa, Zahara
ABSTRACT: The low level of participation of women in the marketing and selling of crops in some patriarchal societies in the developing world has been documented. This article uses a case studies approach to document in detail two successful Agricultural Innovation Platforms (AIPs), out of nine studied, in order to understand what makes a successful AIP. The study shows that AIP activities in Rwanda are contributing to the achievement of gender mainstreaming through the equitable sharing of benefits supported by social, policy, and capacity factors. The article then provides evidence of how such policy or social factors are operationalized; how AIPs utilize policy; and how AIP processes integrate with local social norms and capital.